INDUSTRI LISTRIK PLTA KOTOPANJANG Vs PERMASALAHAN LINGKUNGAN - Aras Mulyadi (JIP ( Jurnal Industri dan Perkotaan ), 2003)
Power plant PLTA Koto Panjang that was built in 1997 is one of energy resourcesthat has great benefit to Riau. For that reason, its sustainability should be retained. Lately,there were environmental problems that became direct threat to the power plant, such asdegradation of catchment area, and erosion and sedimentation. Both of them are caused byintensive land conversion in the upper area.